Analisis Potensi Penerimaan Pajak Daerah Dan Retribusi Daerah Kota Pematangsiantar - Asmawati Asmawati; Amran Saragih; Nora Januarti Panjaitan; Christina Kumala (Politeknik Ganesha Medan, 2019)
Local tax revenues and levies, especially in the city of Pematangsiantar, have not been fully implemented effectively and optimally because one of them is the regulations on tax collection and sanctions for violations that have not been fully enforced. As a developing area, the city of Pematangsiantar should manage sources of income that can be used in development to improve public services in a real and sustainable manner. The potential that exists in Pematangsiantar City must be managed optimally, seen from the number of restaurants and hotels in Pematangsiantar City, an indication that if the government is serious in handling taxes, the revenue that will become Pematangsiantar City's income will increase. However, it is estimated that the main problems in the study of tax potential are not insignificant, mainly related to administrative performance as well as taxpayer compliance. For this reason, a solution is needed how to make efforts to increase tax revenue